1975
DOI: 10.1021/ac60357a009
|View full text |Cite
|
Sign up to set email alerts
|

Separation and detection of low concentrations of polythionates by high speed anion exchange liquid chromatography

Abstract: but the LC water/methanol gradient technique did not separate the parent compound from the major metabolic product, hydroxy-naphthalene. Both compounds were, however, readily identified in the mass spectra corresponding to a single LC peak. Furthermore, an LC/MS combination obviates the need for the high purity, optically transparent solvents used with UV-detection systems. The use of the membrane device, however, limits the solvents to readily volatile, polar compounds.An LC/MS interface can be, therefore, of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Concentrations of S2O3 2~ in tailing pond effluents have been estimated to be in the range of 500 mg/L. 8 Although the chemical nature of organic S in soils has been under investigation for the past three decades, little is known about the organic S compounds present in soils. Early work showed the presence in soils of organic S compounds such as trithiobenzaldehyde, 9 and free cystine.…”
Section: Forms and Sources Of S In Soilsmentioning
confidence: 99%
“…Concentrations of S2O3 2~ in tailing pond effluents have been estimated to be in the range of 500 mg/L. 8 Although the chemical nature of organic S in soils has been under investigation for the past three decades, little is known about the organic S compounds present in soils. Early work showed the presence in soils of organic S compounds such as trithiobenzaldehyde, 9 and free cystine.…”
Section: Forms and Sources Of S In Soilsmentioning
confidence: 99%
“…In the absence of alcohol, thiosulfate could be determined at levels as low as 10 -6 M. This is because thiosulfate reduces Ce(IV) to Ce(III), 14,16 as shown in Eq. (1), and the detection limit for Ce(III) is around 10 -6 M. The detection limit for thiosulfate under these conditions was calculated as 3.0 × 10 -7 M (S/N = 3).…”
Section: Resultsmentioning
confidence: 99%
“…Several sensitive and selective detection methods have utilized a postcolumn reaction of thiosulfate with Ce(IV), followed by fluorescence detection of the resulting Ce(III). [16][17][18][19] Ce(IV) is susceptible to reduction by reducing agents to form Ce(III), and measurement of the resulting Ce(III) can allow the determination of the reducing agent. Ce(III) has a characteristic fluorescence with an excitation maximum at 260 nm and an emission maximum at 350 nm, while Ce(IV) does not fluoresce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that fluorescence spectra for cerium(III) and TX were obtained at 365 nm and 450 nm, respectively. Cerium(IV) is non‐fluorescencent . When TX mixed with cerium(III) in HNO 3 , the fluorescence emission showed a broad peak at 367 nm and a very weak peak at 456 nm.…”
Section: Resultsmentioning
confidence: 99%